La percepción de los estudiantes sobre las Tutorías de Acogida en la Universidad de las Artes de Ecuador: http://repositorio.ulvr.edu.ec/handle/44000/4047 - Guerrero Bocanegra , Borja (2020)
Within the university environment, tutoring is presented as a professional competence, a teaching strategy, an indicator of institutional quality and the passage of an approach based on the figure of the teacher as an expert to that of the student as the center of the teaching-learning process. This article focuses on the Foster Tutoring plan offered by the Guayaquil University of the Arts and is linked to the research project without funding from the institution itself, entitled Methodologies with an intercultural approach for foster tutoring. Case study: University of the Arts of Ecuador under the code VIP-2018-054. The research, which was carried out between the months of April and August 2019, has as its main objective to know the perception of the students towards the host tutorials and the exploration of possible topics to be dealt with in their future development. The research method used was a mixed approach, the instrument designed: Scale of attitudes of university students towards foster tutoring, was applied to the entire beneficiary population of these tutorials. In a complementary way, open-ended questionnaires were used to develop the qualitative approach, where aspects of reflection on art-artist, identity, university life, hetero-perception and experience as students were discussed. The results show the importance and utility of these tutorials, which are considered by students as a motivating space, conducive to academic and personal development. Faced with the positive attitudes of the students, it is suggested to promote and extend the tutorials throughout the entire university career.